DANH HIỆU ĐỊA LÝ CÁC VÙNG BIỂN VÀ HẢI ĐẢO VIỆT NAM VỀ TÀI NGUYÊN VÀ MÔI TRƯỜNG PHỤC VỤ PHÁT TRIỂN BỀN VỮNG - Toán, Dư Văn (Nhà xuất bản Nông nghiệp, 2016)
The article introduces an overview of some national and international geographical titles that have been given to certain Vietnamese marine areas. The awarding of these titles particularly Vietnam's sea areas, has been very helpful for Vietnam. In particular, the granting of international titles by UNESCO to areas on the coast and at sea, such as Ha Long Bay, Phong Nha - Ke Bang and My Son, has had the effect of bringing about great economic development. Regarding the various kinds of titles, the most common international title granted is that of ‘World Biosphere Reserve’, awarded to six sites, followed by ‘World's Most Beautiful Bay’ for three sites, and then two World Heritage sites. At the national level, the most common title awarded has been to the 16 Marine Protected Areas, followed by National Parks with seven titles, and then Nature Conservation Areas with three titles. The economic, social and environmental impact of these titles for marine areas for the Government and Province has been very good. Recommendations for making plans, strategies, and honor levels to recognize geographical titles of Vietnamese marine territories, have special value for the areas and for the agencies and individuals, who have contributed to the work. The article also suggested the need to establish national agencies for the management, approval and recognition of local, national and international titles.